How to render pauperism self-supporting . with practical hints for developing the system of re-productive employment, as a substitute for idleness and useless tests; suggested by a visit to the Cork Union Workhouse.; (N.pl.)
Extracted from "The South of Ireland in 1850", and re-publ. by the Poor-Law Association.